2018
DOI: 10.1136/gutjnl-2017-315363
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication treatment and the risk of gastric adenocarcinoma in a Western population

Abstract: Eradication treatment for seems to counteract the development of gastric adenocarcinoma and non-cardia gastric adenocarcinoma in this Western population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 18 publications
1
77
0
3
Order By: Relevance
“…79 Recently, incremental data has demonstrated that eradication treatment for H. pylori could reduce the risk of gastric cancer. 80,81 Collectively, these studies indicate that gastric microbiota is involved in gastric carcinogenesis. With enormous microorganism at close proximity to the colonic epithelial cells, the involvement of gut microbiota in colorectal carcinogenesis is becoming clear.…”
Section: Fmt For Digestive System Cancersmentioning
confidence: 81%
See 1 more Smart Citation
“…79 Recently, incremental data has demonstrated that eradication treatment for H. pylori could reduce the risk of gastric cancer. 80,81 Collectively, these studies indicate that gastric microbiota is involved in gastric carcinogenesis. With enormous microorganism at close proximity to the colonic epithelial cells, the involvement of gut microbiota in colorectal carcinogenesis is becoming clear.…”
Section: Fmt For Digestive System Cancersmentioning
confidence: 81%
“…Significant enrichment of Peptostreptococcus stomatis , Parvimonas micra , Streptococcus anginosus , Dialister pneumosintes , Slackia exigua, Clostridium colicanis and Fn and depletion of Helicobacterium was observed in gastric cancer, and alterations in bacterial diversity and abundance in patients with gastric cancer revealed a dysbiotic microbial community with prediction potential . Recently, incremental data has demonstrated that eradication treatment for H. pylori could reduce the risk of gastric cancer . Collectively, these studies indicate that gastric microbiota is involved in gastric carcinogenesis.With enormous microorganism at close proximity to the colonic epithelial cells, the involvement of gut microbiota in colorectal carcinogenesis is becoming clear.…”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 91%
“…According to Suzuki et al [31], H. pylori infection can produce pathological changes similar to LGIN, and after eradication of H. pylori infection, the pathological manifestations of atypical hyperplasia can be improved or even reversed with subsidence of active gastritis. Doorakkers et al [32] reported that the risk of gastric adenocarcinoma decreased over time after eradication treatment, to levels below that of the corresponding background population. This suggests that it is important to treat H. pylori as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, long‐term H pylori infection can lead to gastric malignancies, which have been demonstrated in both human and animal models; thus, H pylori has been recognized as a class I carcinogen by the International Agency for Research on Cancer . Recently, a number of clinical studies have demonstrated that the earlier H pylori eradication therapy is given, especially prior to the development of precancerous lesions, the more effective it will be in reducing the risk of gastric cancer . Therefore, nationwide eradication therapy has been implemented in some countries, such as Japan and Korea, which is considered the primary prevention method for gastric cancer …”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, a number of clinical studies have demonstrated that the earlier H pylori eradication therapy is given, especially prior to the development of precancerous lesions, the more effective it will be in reducing the risk of gastric cancer. [3][4][5] Therefore, nationwide eradication therapy has been implemented in some countries, such as Japan and Korea, which is considered the primary prevention method for gastric cancer. 6,7 With the increase in antibiotic resistance, the clarithromycin-or metronidazole-based standard triple therapy for H pylori infection is no longer recommended in China because of its low efficacy.…”
Section: Introductionmentioning
confidence: 99%